2007
DOI: 10.1111/j.1439-0396.2007.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diets supplemented with organic acids and nucleotides on growth, immune responses and digestive tract development in weaned pigs

Abstract: Sixty-eight (Experiment 1, 46 days feeding) and sixteen (Experiment 2, 21 days feeding) 21-days-old weaned pigs were allotted to four dietary treatments including control, 0.6% organic acids (OA), 0.1% nucleotides (NA) and 0.6% OA plus 0.1% NA for determining the dietary effects. In Experiment 1, OA enhanced peripheral blood mononuclear cells proliferation on day 28 and 46. The plasma immunoglobulin (Ig) A level was elevated by OA (p < 0.06) and NA (p < 0.07), respectively. In Experiment 2, NA increased plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 29 publications
(38 reference statements)
7
39
2
3
Order By: Relevance
“…Moreover, intestinal lymphocyte maturation and mRNA abundance of IL-6 and IL-8 were also enhanced by dietary nucleotides (Gil 2002). In addition, exogenous nucleotides stimulated humoral immune response and production of immunoglobulins in neonates and weaned piglets (Maldonado et al 2001;Lee et al 2007;Sauer et al 2012a). In contrast, the restriction of dietary nucleotides resulted in a decreased production of IL-2, natural killer cell cytotoxicity, and macrophage activation (Carver 1994).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, intestinal lymphocyte maturation and mRNA abundance of IL-6 and IL-8 were also enhanced by dietary nucleotides (Gil 2002). In addition, exogenous nucleotides stimulated humoral immune response and production of immunoglobulins in neonates and weaned piglets (Maldonado et al 2001;Lee et al 2007;Sauer et al 2012a). In contrast, the restriction of dietary nucleotides resulted in a decreased production of IL-2, natural killer cell cytotoxicity, and macrophage activation (Carver 1994).…”
Section: Discussionmentioning
confidence: 93%
“…Da mesma forma, a inclusão de 1,0% de glutamina na ração, em estudo conduzido por Kitt et al (2002), não influenciou a altura de vilosidades de leitões desmamados aos 18 dias de idade. Da mesma forma, Lee et al (2007) avaliaram a inclusão de nucleotídeos na ração de leitões desmamados em mesma idade e não notaram efeito sobre a morfologia intestinal aos 35 dias de idade.…”
Section: Itemunclassified
“…However, N Sauer, M Eklund, S Roth and R Mosethin (unpublished results) could not confirm these findings in a study with piglets fed a commercial product containing nucleotides, since a-amylase, maltase, lactase and leucine aminopeptidase activities in ileal digesta on days 13 and 20 after weaning were not affected. Furthermore, Lee et al (44) found an increase in gastric pepsin and jejunal alkaline phosphatase activity, associated with a decrease in ileal aminopeptidase, sucrase and maltase activity, following the supplementation of the diet for weaned pigs with 0·1 % of a commercially available nucleotide product. Moreover, a study with rats revealed that withdrawal of dietary nucleotides led to a decrease in the content and specific activity of alkaline phosphatase, leucine aminopeptidase, maltase, sucrase and lactase in the villous tip (78) .…”
Section: Biological Effects Of Dietary Nucleotidesmentioning
confidence: 99%
“…Moreover, they also secrete various cytokines such as interferon-g, TNF-a and IL-2 (108,109) , which may play an important role in immune modulation at the mucosal surfaces. Furthermore, Lee et al (44) demonstrated an immunomodulating effect as indicated by increased levels of plasma immunoglobulins (IgA, IgM) in weaned pigs when fed a commercial product containing nucleotides at 0·1 %. A study by Cameron et al (96) revealed that feeding nucleotides to early-weaned piglets may enhance T-cell functions in delayed hypersensitivity to antigenic challenge in the intestine and in vitro lymphocyte proliferation response to concanavalin A, a mitogen which stimulates T-lymphocytes.…”
Section: Immunological Effectsmentioning
confidence: 99%
See 1 more Smart Citation